Práticas pedagógicas inclusivas para alunos surdos numa perspectiva colaborativa. - Zanata, Eliana Marques (2004)
The practice of inclusion in the school involves the education of children with special educational needs in regular classrooms with colleagues without special needs. However, regular education teachers are inclined to change practices as to arrangements, instructional procedures, activities, assessments and adequacy of the contents, so as the participation and learning of these students may be impaired. Even though the literature of inclusion presents many effective pedagogical strategies, they do not seem to reach the classrooms of deaf students. The present study is based on the problem of achieving better teachers qualification, attempting to enhance the pedagogical practices of regular education teachers as regards the needs of deaf students. The study comprised establishment and evaluation of a continued education program for regular education teachers so as to make it more autonomous and provide more effective adequate pedagogical practices to the needs of students. The study was conducted for 20 weeks and involved the researcher acting as a collaborator and three different teachers who had deaf students in their classrooms. The fist part involved a preliminary planning for analysis of the learning style of deaf students, and the aims and strategies that would be used with these students along the year. This was followed by collaborative intervention, on which the researcher videotaped a random class of each teacher. This tape was edited and presented in a meeting for the three teachers, for analysis and re-planning if required. Each class was re-planned and enhanced until all teachers agreed that the goal had been achieved. The collected data involved initial educational planning protocol and the protocol of each class with complete recording of the processes since the initial planning until evaluation of the last successful implementation. The teaching processes of 64 classes were videotaped, with a mean of 16 to 26 classes per teacher. The meetings also comprised discussion about texts on inclusive pedagogical practices. After intervention, the teachers opinions on the collaborative planning activity were gathered. The results showed many possibilities to establish a collaborative environment between regular education and special education teachers. The planned strategies were implemented in classrooms, and intervention provided an opportunity of training for the teachers. The teachers evaluated that the strategies implemented benefited not only the deaf students, but also the others. The collaboration potential between regular education and special education teachers is discussed as a strategy for formation and facilitation of inclusion of students with special educational needs. The results further demonstrated that, even though collaborative intervention has enhanced the quality of teaching, it does not seem to be enough to solve the communication problems between teacher and deaf student.